Effect of the addition of collagen and sucralose on the technological and sensory characteristics of yogurt (Research, Society and Development, 2021)
Recently, the protection and treatment of skin diseases with dietary supplements has received increasing attention. One example is collagen peptides that improve skin aging induced by ultraviolet radiation. In this sense, the present work aimed to evaluate the influence of the addition of collagen and sucralose on the technological and sensory characteristics of yogurt through a factorial design with 2 independent variables (X1 = collagen, 0.625 to 1.25% and X2 = sucralose, 0.02 to 0.04%). The dependent variables studied were: total titratable acidity, water holding capacity, acceptance and sweetness. Through the Response Surface methodology, it was observed that the independent variables collagen and sucralose had statistically significant effects (p